Profiles of recreational activities of daily living (RADL) in patients with mental disorders - Linden, Michael (Array, 2009)
Activities of daily living, play a key role in the measurement of functional health as defined by the International Classification of Functioning, Disability and Health (ICF) and in prevention and treatment of mental or somatic illnesses. The data give a reference profile for recreational activities, help to define what can be considered a normal frequency and spectrum of RADL, and, by this, can guide therapeutic interventions.